Hormones, Food, Stress And Infections: Their Etiological Role In Autoimmune Diseases - Rodríguez Manso, Amanda; González-Costa, Maricarmen; Padrón González, Alexander Ariel (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: The etiology of autoimmune diseases is still unknown, but different causes arise. Objective: To describe the role of hormones, diet, stress and infections in the etiology of autoimmune diseases. Material and Methods: A bibliographic review was made using the Google Scholar and articles of free access in the Pubmed and Scielo database from 2015 to 2019. The search terms were used according to the DeCS and MeSH descriptors. Development: It is well known that female hormones increase the risk of autoimmune diseases. Stress can maintain low-grade chronic inflammatory responses that cause tissue damage, initiating or aggravating the clinical manifestations of autoimmunity. An adequate diet allows the guests of the intestinal microbiota to maintain the homeostasis of the immune system. Today, glutamate is used as a flavor enhancer, especially in developed countries. Perhaps it is one of the causes of the higher incidence of autoimmune diseases in these regions. Conclusions: Autoimmune diseases are more frequent in women. Adequate nutrition allows the gut microbiota not to be altered and to maintain immunological homeostasis. Infections and stress situations can trigger or exacerbate the clinical manifestations of autoimmunity.